Dental e-learning before, during and after COVID-19 pandemic: a cross sectional study among Saudi dental students - Basudan, Amani M.; Almubarak, Abdulrahman M.; Al-Zawawi, Abeer S.; Al-Ahmari, Fatemah M.; Aldulaijan, Hajer A.; Almoharib, Hani S.; Shaheen, Marwa Y.; Ashri, Nahid Y. (International Journal Of Community Medicine And Public Health, 2023)
Background: Dental education has been shifting from face‑to‑face learning to e-learning, and this was profound during the COVID-19 pandemic. This study aimed to assess the overall experience and satisfaction of dental students towards e-learning in Riyadh, Saudi Arabia, before, during, and after the COVID-19 pandemic. Methods: A cross-sectional questionnaire-based study was conducted between November 2022 and January 2023. The survey questionnaire comprised items for both qualitative and quantitative analysis of data. Non-parametric tests (Mann-Whitney U test and Kruskal-Wallis test along with Conover post-hoc analysis) were conducted to compare ‘e-learning experience’ and ‘overall satisfaction’, against the descriptive variables. Results: The sample of 250 participants comprised 52.4% females, 71.6% were in the age group 22 to 25 years, 96.4% were Saudi nationals, and 29.6% were 4th-year students. Approximately 72.8% of them described their IT skills as average and 55.2% of them had participated in e-learning activities before the COVID-19 pandemic. E-learning for practical/clinical sessions before the COVID-19 pandemic lockdown, during the complete lockdown, after partial return following the lockdown, and after complete return following the lockdown are statistically significantly higher in participants who had participated in e-learning before the pandemic. Conclusions: The present study ascertained the positive perceptions of dental students regarding e-learning as a preferred learning method. However, the students of the preclinical and clinical years have a varying preference between traditional face-to-face education and online learning.